Envolvimento de cuidadores no programa educacional de pessoas com autismo e deficiências severas: o que é e como medí-lo? - Assunção, Karine Ribeiro de (Universidade Federal de São Carlos, 2004)
The involvement of the family in the special education of handicapped individuals has been raising of researchers who try to identify involvement behaviors and elaborate specific strategies to each family, in order to help them in dealing with the different aspects of the child s life. Researches indicate that parents participation is stile limitaded and passive. Literature affirms that the involvement is articulated with multiple factors, which are found in the family, school and social enviroment. The few studies consider parents involvement in a educational program of young people with special needs, principly when they have severe limitations. The present study has as its objective to elaborate tools of evaluation of parents involvement in the educational program of individuals with special needs and identify the involvement of one of the parents of autistas and severe handicapped individuals and correlate with aquisition habilities in the basic activities of the students. We also tried to look for the answer if the number weekly attending offered by the school influenced parents involvement. Participated in this study thirty eight careers, whose students attend school for individuals with special needs, in Ribeirão Preto. This evaluation was based in specific literature data and also writer teachers and parents. It was also used a tool of the school for assessment of the aquisition of habilities in basic activities. Statistic analysis through Pearson s correlation indicate that there isn t correlation between students performance in basic habilities aplicatade and involvement in educational process, although there as a high positive correlation between the performance of the students between asnwer by careers and teachers. Important mention that the gain for students in basic habilities were little.
Keywords: Educação especial; Educação participação dos pais; Desempenho; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL